Novel Technology for Treatment of Acidic Wastewater Containing Mercury in Zinc Smelter by Biologics - Qingwei Wang (The Minerals, Metals and Materials Society, 2009)
This study focused on acidic wastewater from producing sulfuric acid system in zinc smelter containing mercury 21.48mg/L, zinc 55.85mg/L, lead 38.50mg/L, copper 1.68mg/L, cadmium 10.25mg/L, As 29.86mg/L treated by biologics. The factors of pH value, the ratio of biologics to mercury, complexing time, hydrolytic time and temperature were studied in this paper. Experimental results indicated that at pH value 10, quantity of biologics to mercury ratio was 16, complexing time 30min, hydrolyzation time 20min, temperature at 40?, concentration of mercury in treated water was removed to 22.15µg/L. At same time heavy metals such as Zn, Pb, Cu, Cd, As was removed by biologics, the remained concentration in treated water was Zn 0.53mg/L, Pb 0.12mg/L, Cu 0.01mg/L, Cd low to 0.01mg/L and As 0.023mg/L. According to EDAX analysis, mercury content in complexing sediment reached 28.49% easily to recycle as raw material and low concentration of heavy metals in hydrolytic sediment easily to dispose and treat.